Climate change and marine benthos: a review of existing research and future directions in the North Atlantic. (6th January 2015) - Birchenough, Silvana N.R.; Reiss, Henning; Degraer, Steven; Mieszkowska, Nova; Borja, Ángel; Buhl‐Mortensen, Lene; Braeckman, Ulrike; Craeymeersch, Johan; De Mesel, Ilse; Kerckhof, Francis; Kröncke, Ingrid; Parra, Santiago; et al.
<x xml:space="preserve">Abstract</x> There is growing evidence that climate change could affect marine benthic systems. This review provides information of climate change‐related impacts on the marine benthos in the North Atlantic. We cover a number of related research aspects, mainly in connection to two key issues. First, is the relationship between different physical aspects of climate change and the marine benthos. This section covers: (a) the responses to changes in seawater temperature (biogeographic shifts and phenology); (b) altered Hydrodynamics; (c) ocean acidification (OA); and (d) sea‐level rise‐coastal squeeze. The second major issue addressed is the possible integrated impact of climate change on the benthos. This work is based on relationships between proxies for climate variability, notably the North Atlantic Oscillation (NAO) index, and the long‐term marine benthos. The final section of our review provides a series of conclusions and future directions to support climate change research on marine benthic systems. WIREs Clim Change 2015, 6:203–223. doi: 10.1002/wcc.330 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.